Easy Access to Crystalline Indolines via Hydrogen Bond Transfer. (19th February 2019) - Khatoon, Saira; Vgenopoulou, Aggeliki; Naseer, Muhammad Moazzam; Shirinfar, Bahareh; Kariuki, Benson M.; Dege, Necmi; Ahmed, Nisar
Abstract : Several indoline derivatives with specific geometries are biologically active and have inhibitor properties. Many indolines are a key part of natural products. Much attention has been focused on the development of synthetic routes for their easy access. Current synthesis depends largely on metal catalysis, iodine reagents, and Oxone. To date, no synthetic route has been established that is metal‐free, reagent‐free, and environmentally friendly and provides a base for green chemistry. Here, we report the first facile metal‐free and reagent‐free synthesis of indoline derivatives, which could potentially be influential in the design of new biologically active compounds. The synthesis proceeds through intramolecular amination between a urea nucleophile and unactivated alkene. The ring closure occurs in a few hours in the presence of pre‐dried silica gel and gives good yields of indolines products, but in the absence of silica gel, the ring closure occurred overnight with stirring in dry solvent. An electron withdrawing group at the substituted aryl moiety of ureas increases the hydrogen bond donor ability of substrates that mediate the internal proton transfer at the terminal alkene and results in facile amination to give the indoline product with an "in plane" orientation of the carbonyl group and aromatic part of indoline framework. Such orientation in indolines is important for potent biological activities. Abstract :